Factors behind Institutional Delivery Preference in the Republic of Benin: An Analysis of 2011-2012 Benin Demographic and Health Survey (BDHS) data - Dansou, Justin; Adekunle, Adeyemi O.; Arowojolu, Ayodele O. (Journal of Population and Social Studies [JPSS], 2018)
Background: Ending preventable maternal and newborn morbidity and mortality remains a core component of the Sustainable Development Goals (SDG) which is a continuation of the Millennium Development Goals (MDG). It has been documented that most women in developing countries give birth at home without the intervention of skilled attendants despite the prevailing multitude risks associated with childbirth for both mother and the unborn child. The study was aimed at identifying the most significant factors influencing selection of health facility based delivery among reproductive age mothers. Data and methods: Data was obtained from Benin Demographic and Health Survey (BDHS) of 2011-2012 using percent distribution, binomial logistic regression and multinomial regression. Out of 16,599 interviewed only 9,111 were eligible for the present study. Results: Most (76.0%) of the respondents gave birth at public health centers, 11% in private health centers and the rest outside health institutions. Out of 17 variables examined, 13 were found (using Akaike Information Criterion in a stepwise algorithm) to be the most important factors for institutional delivery. Among them, Antenatal Care (ANC) frequency, mother’s education, and household wealth index had most impact on institutional deliveries with positive and linear relationships. Most of the educated women (secondary or above) were more likely to give birth in a private health facility (Private Health OR=5.2, 95% CI 2.47-10.88; Public Health OR=3.7, 95% CI 1.82-7.6). Similar results were found among the richest women (Private Health OR=8.6, 95% CI 3.5-21.3; Public Health OR=4.4, 95% CI 1.90-10.4). Female education and economic status were the most important factors for institutional delivery preference. Conclusion: Encouraging regular ANC visits (at least the four recommended visits), and girls’ education up to secondary school will help getting women to deliver in a well-equipped health facility. There is also a need to investigate thoroughly through qualitative researches reasons behind their preference of health facility for reproductive health services, including institutional delivery.